Processing of nano fillers in nitrile rubber – A novel technique - Abitha, V.K.; RANE, Ajay Vasudeo; Rajkumar, K. (Journal of Metals, Materials and Minerals, 2015)
Dispersion of various nano fillers like Nano silica, nano clay, Nano TiO2, etc has been attempted in NBR rubbers using new technique of dispersion. Liquid NBR is taken as dispersion media for nano fillers in polymer matrix and polymer nano composites were characterized by Rubber Process Analyzer [RPA-2000, USA]. The dispersion of the nano fillers were investigated by XRD, SEM-EDS. The effect of increasing nano- fillers on mechanical properties like tensile strength, modulus and Elongation at break was studied. Hot air ageing of polymer nano composites was also studied. Dispersion of various nano fillers like Nano silica, nano clay, Nano TiO2, etc has been attempted in NBR rubbers using new technique of dispersion. Liquid NBR is taken as dispersion media for nano fillers in polymer matrix and polymer nano composites were characterized by Rubber Process Analyzer [RPA-2000, USA]. The dispersion of the nano fillers were investigated by XRD, SEM-EDS. The effect of increasing nano- fillers on mechanical properties like tensile strength, modulus and Elongation at break was studied. Hot air ageing of polymer nano composites was also studied.